THE EFFECT USAGE WASTE OF WINE AS FEED TO PHYSICAL QUALITY OF LOCAL MALE RABBIT (Lepus nigricollis) - M., Purwaningsih; Nuriyasa, I M.; Sriyani, N. L. P. (Jurnal Peternakan Tropika, 2017)
The purpose of this research was to determine the effect usage waste of wine as feed to physical quality of local male rabbit (Lepus nigricollis) meat. This research was conducted in Tejakula Village, Buleleng Regency and conducted 16 weeks used 18 local male around 5 – 6 weeks old. This research used randomized block design with three treatments and six blocks as replicates. The treatments were local male rabbits without waste of wine on diets as control (P0), local male rabbits with 5 % waste of wine on diets (P1), and local male rabbits with 10 % waste of wine on diets (P2).  The variables in this reasearch were acidity of color meat, pH of meat, water holding capacity of meat, cooking loss, and drip loss. The results showed that rabbit offered diets containing different level waste of wine caused non significant different (P>0,05) to physical quality of local male rabbit meat. Based on the results of the research can be concluded that usage 5 % and 10 % waste of wine on diets not affected to physical quality of local male rabbit meat. Keywords : local rabbit, physical quality of meat, waste of wine.